The traditional livestock breeding practices of women and men Somali pastoralists: breeding management and beliefs on breeding issues - Marshall, Karen; Mtimet, Nadhem; Wanyoike, Francis N.; Ndiwa, Nicholas; Ghebremariam, Haileselassie; Mugunieri, Lawrence; Costagli, Riccardo (Commonwealth Scientific and Industrial Research Organisation, 2019)
In Somalia, located in the horn of Africa and one of the world’s poorest countries, livestock are the mainstay of the economy. While strengthening the livestock sector is considered key to reduced poverty and increased food security, few studies have reported the livestock management practices of Somali pastoralists, including on breeding issues. Here, we present the final of a series of papers documenting the breeding practices of women and men Somali pastoralists for goat, sheep, camel and cattle. Data for the study were obtained by surveying 200 livestock-keeping households located within the Tog-Dheer region of Somaliland. The most important livestock species kept, in terms of contribution to household livelihood, were goats and sheep, followed by camel, then cattle. Migration with livestock was practiced by two-thirds of the households for some or all of the year, whereas other households were settled with their livestock. On breeding practices, the main means of acquiring breeding animals was by the animal being born into the herd, and varied means were used to control mating, including castration, culling, separation of male and female animals, purposeful mating of best males to best females, and controlling the size of mating groups. On beliefs on breeding issues, the pastoralists had a varied understanding of whether specific livestock traits were influenced by genetics, environment, or a combination of both, and most could not articulate the basis of inheritance. Knowledge of inbreeding was poor, with almost all respondents indicating they did not consider the mating of related animals to be problematic. Additionally, some pastoralists tried to influence the sex of the livestock progeny born through various practices. Overall, the finding presented here and in the companion studies (Marshall et al. 2014, 2016) indicated that the women and men Somali pastoralists generally employ sound breeding practices, although there is room for capacity building such as on inbreeding.